Impact of Teacher Violence on Academic Performance of Undergraduates of Imo State University - Ipem, J. N.; Alaribe, C. O.; Jimoh, M. I.; Okoye, A. O.; Emeka, I. D. (Journal of Research in Adult and Continuing Education, 2024)
The study investigated the impact of teacher violence on academic performance of undergraduates of Imo State University, Owerri. Three specific purposes in line with three research questions guided the study. Descriptive survey design was adopted for the study. The population of the study comprises all the undergraduates in the 23 faculties in Imo State University, Owerri totaling 40, 201 students. Stratified random sampling technique was used to draw a sample size of 400 across all levels of undergraduates’ students. The researcher developed the instrument for data collection titled: Teacher Violence and Students Academic Performance Rating Scale (TVSAPRS). The instrument for data collection was validated by three experts, two from Educational Measurement and Evaluation and one from Educational Psychology. The reliability coefficient of the instrument was established as 0.88 using the Pearson’s Product Moment Correlation Formula and test and retest method. Mean and standard deviation were used to answer the research questions and the findings identified some forms of violence exhibited by teachers in Imo State University Owerri which include among others as: threatening to deal with students or fail them, sexual harassment, touching in a sexual manner without consent, calling them abusive names, physical and emotional assaults. It was found that to a large extent, teacher violence on student affect their academic performance negatively. It was recommended among other things that university administrators should organize seminars and workshops for teachers on the dangers of their violent behaviours on students’ academic performance; the university should ensure that the school manual (handbook on rules and regulations) are followed by both students and teachers/lecturers. School authorities should device measures to deal with any teacher found guilty of the act.